2007
DOI: 10.1080/02699050701481589
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic alliance in post-acute brain injury rehabilitation: Predictors of strength of alliance and impact of alliance on outcome

Abstract: Findings indicate that family perceptions and family functioning are important determinants of therapeutic alliance for patients in PABIR. These results indicate that therapists in PABIR programmes should address family perceptions and functioning to facilitate patient bonding with the programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 22 publications
1
55
2
2
Order By: Relevance
“…They are often individually tailored and occur as part of complex systems (health and social care, employment, and education) that are prone to modification. They may be influenced by many potential 'confounders' other than the intervention in question: for example, by environmental factors (such as where the intervention takes place and access barriers -for instance, transport), treatment intensity, the therapist's expertise, whether and how feedback is given, and both 'therapist' and 'patient' factors such as personality, warmth, and communication skills, how the patient engages with the therapist and/or process, motivation, and effort (Sherer et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…They are often individually tailored and occur as part of complex systems (health and social care, employment, and education) that are prone to modification. They may be influenced by many potential 'confounders' other than the intervention in question: for example, by environmental factors (such as where the intervention takes place and access barriers -for instance, transport), treatment intensity, the therapist's expertise, whether and how feedback is given, and both 'therapist' and 'patient' factors such as personality, warmth, and communication skills, how the patient engages with the therapist and/or process, motivation, and effort (Sherer et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Algunos estudios han mostrado que el involucramiento efectivo de las familias se relaciona con mejorías funcionales (45) y de adaptación46 en pacientes con ACV. Por el contrario, altos niveles de desacuerdo entre la familia y el equipo, respecto al funcionamiento del paciente, se asocia con una escasa alianza de trabajo y menor colaboración en el proceso de rehabilitación (47).…”
Section: C-la Participación Activa De La Familiaunclassified
“…Additional results cited previously may support the value of a therapeutic alliance from a comparison of TBI to other conditions. However, a study evaluating the relationship between alliance and outcomes found that therapeutic alliance strength was associated with remaining in postacute brain injury rehabilitation but not with functional status at discharge [86]. A survey of psychologists working on psychological sequelae of TBI endorsed the need to build the therapeutic alliance, and this group frequently employed a variety of techniques to strengthen it, including education about TBI and its emotional consequences, memory aids, shorter or more focused therapy sessions, involvement of family members, and behavioral techniques to help the patient better understand post-TBI functional limits [87].…”
Section: General Principles For Managing Ptsd In Combat Veteran With Tbimentioning
confidence: 99%